Newly qualified in-service teachers’ readiness for pedagogical technology use in the classroom: case studies of township schools - Vilakazi, Naledi (University of the Witwatersrand, Johannesburg, 2024)
Newly qualified teachers in South African townships face a critical challenge: integrating technology effectively into classrooms to prepare learners for the demands of Education 4.0 and the Fourth Industrial Revolution (4IR). Education 4.0 and the 4th Industrial Revolution (4IR) necessitate seamless digital technology integration, yet many teachers lack the skills and knowledge to leverage its potential (Oke & Fernandes, 2020). The study aims to investigate the preparedness of newly qualified in-service teachers in township schools for integrating pedagogical technologies into their classrooms. By using case studies, the research explores the factors influencing their readiness for effective technology use in the learning environment. The study uses a qualitative method for data collection, specifically in-depth interviews, to explore teachers' perspectives on technology integration. Purposive sampling was employed to select six teachers from township secondary schools, ensuring rich and relevant data collection (Creswell, 2013). Thematic analysis revealed a complex landscape marked by uneven adoption of digital tools, inadequate teacher training, and limited resources. The findings exposed this mismatch; the Activity Theory highlighted the contradictions faced by the newly qualified in- service teachers – they are expected to integrate technology yet lack the tools and knowledge to effectively mediate student learning activities with technology as an object. This research offers valuable insights for policymakers and educators. The study recommends the creation inclusive learning environments that consider the socio-economic realities of township schools and teacher training programs with pedagogical approaches that utilize technology for transformative learning.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Digital Technologies; Digital Pedagogical Affordances; Communities of Practice; newly qualified-In-Service Teachers; Forth Industrial Revolution; Professional Development; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure